PENGARUH MODEL PEMBELAJARAN TALKING STICK TERHADAP PEMAHAMAN DAN MOTIVASI SISWA SD KELAS 5B PADA MATA PELAJARAN MATEMATIKA DI SD MUHAMMADIYAH 1 BANGKALAN - Riezal Muhaimin; Ihwan Firmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aimed to assess the influence of the talking stick learning model on students' comprehension and motivation at SD Muhammadiyah 1 Bangkalan. The quantitative method employed was a Pre-Experimental Designs experiment using a One Group Pretest-Posttest Design. The study utilized tests for validity, reliability, normality, and the Paired Sample T-Test Hypothesis in data analysis. Results indicated a significant improvement in student comprehension and motivation, as confirmed by SPSS analysis validating its high impact. The Paired Sample T-Test showed a noteworthy increase in motivation (from 14.35 to 36.00) and comprehension (from 5.54 to 13.46).